Seismic characteristics, distribution and origin of shallow gas on the continental shelf offshore the Pearl River Estuary, northern South China Sea - Jian Li; Wei Li; Tiago M. Alves; Yingci Feng; Jie Sun; Yantao Yao; Jiaxian Huang; Pin Wang; Qinqin Tang; Wenhuan Zhan (Marine Geology, 2026)

Predictive model of perchlorate adsorption by imidazole-N modified activated carbon: Experimental validation and mechanistic analysis - Xinyu Sun; Jianhui Guo; Jianbing Wang; Jiushuai Deng; Cesar Niedo-Delgado; Chunrong Wang; Pin Hou (Journal of Water Process Engineering, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Development of magnetic solid-phase extraction with magnetic graphene oxide composite nanospheres for sensitive determination of perfluoroalkyl substances in tea beverages - Xin-Li Song; Tong Sun; Ke-Chao Liao; Hui Lv; Pin-Pin Wang; Dong-Dong Wang; Yan Lu; Lin Li (Analytica Chimica Acta, 2026)

Synergistic microbubble ozonation and CaO2 activation for refinery sludge valorization: Organic carbon liberation and petroleum hydrocarbon degradation - Di Shu; Ziyang Lou; Kaiyan Yang; Zhiyi Sun; Hui Wang; Zhaowen Cheng; Pin Zhou; Shuping Zhang; Nanwen Zhu; Luochun Wang (Journal of Environmental Management, 2026)

Changes in decomposition rates and nutrients of leaf litter and fine roots in urban tree species under ozone pollution - Xiaofan Hou; Pin Li; Yuqian Sun; Chenhan Ma; Jing Fu; Weixia Huang; Zhuoran Zou (Urban Forestry & Urban Greening, 2026)

WS2-modified schwertmannite for highly efficient dye wastewater degradation via enhanced Fe cycle in heterogeneous Fenton-like catalysis - Kun Feng; Shuping Zhang; Neng Tao; Zhiyi Sun; Xianqiang Kong; Yuanyu Tan; Xuhao Liu; Lixiang Zhou; Pin Zhou; Yongjun Shen; Ting Li (Journal of Environmental Sciences, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Biomimetic microneedle patch integrating ROS-scavenging nanoceria, anti-inflammatory phytochemical, and macrophage-membrane-coated nanoparticles for local hepatic therapy of endotoxemia - Bingwen Zhu; Chang Sun; Dongrong Luo; Zhongliang Zhang; Linguo Cao; Tao Bi; Aolin Jiang; Yuying Liang; Zehui Jiang; Haihua Luo; Pin Jiang; Shaoqing Liu; et al. (Chemical Engineering Journal, 2026)

Artificial intelligence transformations in geotechnics: progress, challenges and future enablers - Brian Sheil; Christos Anagnostopoulos; Róisín Buckley; Matteo Oryem Ciantia; Eky Febrianto; Jinlong Fu; Zhiwei Gao; Xueyu Geng; Bin Gong; Kevin Hanley; Pengpeng He; Kostas Kolomvatsos; et al. (Computers and Geotechnics, 2026)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

Dietary Supplementation with Multi-strain Probiotic Formulation (Bifidobacterium B8101, Lactobacillus L8603, Saccharomyces bayanus S9308, and Enterococcus SF9301), Betaine or their Combination Promotes Growth Performance Via Improving Intestinal Development in Broilers - Dan Hu; Xiaoting Wu; Pin Song; Manman Hou; Li’an Pan; Xiaoran Yang; Qinwei Sun; Yingdong Ni (Probiotics and Antimicrobial Proteins, 2025)

Novel insights into the effect of sTIM-3 on NLRP3 inflammasome via interacting with ASC - Xiaodi Zhang; Na Han; Ziqing Xu; Zheng Tong; Xiaolei Ren; Yang Sun; Chunyang Li; Xuetian Yue; Zhuanchang Wu; Xiaohong Liang; Chunhong Ma; Pin Wang; et al. (Inflammation Research, 2025)

Peroxymonosulfate activation by iron-sulfur tailings doped with SiO2 for efficient degradation of tetracycline - Chen-Chen Yin; Chun Cheng; Peng-Yu Zhang; Zheng-Yuan Zhang; Ying Qin; Li-Pin Xue; Yu-Qi Feng; Bai Sun; Shu-guang Zhu (Environmental Science and Pollution Research, 2025)

Investigation of the ecological roles of the plastisphere microbiome in metal-contaminated river sediments: elucidation of their metabolic versatilities for plastics mineralization and metal resistance - Tianle Kong; Xiaoxu Sun; Pin Gao; Wei Huang; Xiaojie Guan; Zhimin Xu; Baoqin Li; Weimin Sun (Water Research, 2025)

In vivo molecular imaging of drug resistance in neuroblastoma using APE1 cyclically cleaved and miR-514a self-recycled programmable allosteric DNA nanomachine - Wancun Zhang; Zhenzhen Tian; Pin Zhang; Lifeng Li; Zhidan Yu; Meng Sun; Kangbo Liu; Ligong Hou; Jie Zhang; Mengxin Zhang; Xianwei Zhang (Chemical Engineering Journal, 2025)

Loss of circular EYA3 attenuates formaldehyde-induced cardiomyocyte pyroptosis and congenital heart defects by regulating Smad5 stability - Ying Zhang; Yanyan Yang; Xiangqin He; Pin Sun; Xiaoxia Song; Yu Tian; Jianmin Ma; Ruicong Sun; Tao Yu; Zhirong Jiang (Science of The Total Environment, 2025)

One-step controllable synthesis of N-doped porous carbon derived from ZIF-8 for efficient capacitive deionization - Pin Hou; Jiaqi Yan; Xiaoyu Yang; Ridha Djellabi; Xinrui Ge; Xinyu Sun; Jianli Jia; Jianbing Wang (Journal of Environmental Chemical Engineering, 2025)

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Geoarchaeological study of the evolution of rice farming fields in prehistoric Yangtze Delta and Huai River regions of China - Yijie Zhuang; Pin Ding; Lina Zhuang; Yonglei Wang; Wenwan Wu; Xia Wang; Yulong Niu; Guoping Sun; Xingtao Wei; Ling Qin (Quaternary Science Reviews, 2025)

Effect of safflower seed oil on the molecular structural and enzyme hydrolysis properties of maize starch-lipid complexes - Wen Tan; Qinjun Zhang; Pin Chen; Qingqing Sun; Changqing Wei; Xinwen Xu; Natthawuddhi Donlao; Jinhu Tian (Food Chemistry, 2025)

Thermal-fluid coupled fracture behavior of fissured granite in a 3D crystal model - Heng Li; Sheng-Qi Yang; Bo-Wen Sun; Zhen Yang; Zhi-Jin Dong; Pin-Qiang Mo (Engineering Geology, 2025)

Oligosaccharide-assisted resolution of holothurian fucosylated chondroitin sulfate for fine structure and P-selectin inhibition - Ying Pan; Huifang Sun; Xi Gu; Sujuan Li; Shengtao Yang; Liang Zhang; Hui Mao; Pin Wang; Shasha Yang; Ronghua Yin; Zhili Zuo; Jinhua Zhao (Carbohydrate Polymers, 2025)

Associations between urinary multiple metal concentrations and mitochondrial DNA copy number among occupational workers - Zhiping Duan; Qinyu Zhang; Yiming Dai; Jiayun Ding; Changhao Cao; Qiang Hou; Ziqian Yang; Pin Sun; Jiming Zhang; Zhijun Zhou (International Archives of Occupational and Environmental Health, 2025)

Metal ions-mediated concerted electron-proton transfer enables catalytic oxidation of phenolic contaminants by permanganate - Tiansheng Chen; Pin Xie; Yanghai Yu; Xiaoguang Duan; Yuankui Sun; Xiaohong Guan (Water Research, 2025)

The Influence of the COVID-19 Pandemic on Pseudomonas aeruginosa Infection in Children, Henan, China - Mengxin Zhang; Meng Sun; Pin Zhang; Ligong Hou; Bang Du; Huanmin Wang; Xianwei Zhang; Wancun Zhang (Indian Journal of Microbiology, 2024)

Optimizing parameter learning and calibration in an integrated hydrological model: Impact of observation length and information - Peishi Jiang; Pin Shuai; Alexander Y. Sun; Xingyuan Chen (Journal of Hydrology, 2024)

Poly (ionic liquid) anchored granular activated carbon for efficient and selective removal of perchlorate: performance, DFT calculations and mechanism - Pin Hou; Xinyu Sun; Jianhui Guo; Chunrong Wang; Cesar Nieto-Delgado; Jianbing Wang (Chemical Engineering Journal, 2024)

Drought stress impacts soil microbial nutrient limitation more strongly than O3 pollution - Pin Li; Yuqian Sun; Xiaofan Hou (Applied Soil Ecology, 2024)

Chromosome-Level Genome Assembly and Comparative Genomic Analysis of the Barbel Chub (Squaliobarbus curriculus) by Integration of PacBio Sequencing and Hi-C Technology - Baidong Zhang; Yanling Sun; Yang Liu; Xiaojun Song; Su Wang; Tiaoyi Xiao; Pin Nie (Fishes, 2024)
The barbel chub (Squaliobarbus curriculus), the only species in the genus, is widely distributed in freshwater lakes and rivers at different latitudes in East Asia, with fishery and biodiversity importance, and is an emerging commercially important fish in China. However, the resource of this species has dramatically declined due to anthropogenic activities such as over-exploitation, as well as water pollution. Genomic resources for S. curriculus are useful for the management and sustainable utilization of this important fish species, and also for a better understanding of its genetic variation in the region. Here, we report the chromosome-level assembly of the S. curriculus genome obtained from the integration of PacBio long sequencing and Hi-C technology. A total of 155.34 Gb high-quality PacBio sequences were generated, and the preliminary genome assembly was 894.95 Mb in size with a contig N50 being 20.34 Mb. By using Hi-C data, 99.42% of the assembled sequences were anchored to 24 pseudochromosomes, with chromosome lengths ranging from 27.22 to 58.75 Mb. A total of 25,779 protein-coding genes were predicted, 94.70% of which were functionally annotated. Moreover, S. curriculus shows resistance to grass carp haemorrhagic disease (GCHD) caused by grass carp reovirus (GCRV), which seriously hinders the status and future perspectives of commercial grass carp production. Phylogenetic analysis indicated that S. curriculus diverged with grass carp (Ctenopharyngodon idellus) approximately 20.80 million years ago. Annotations of the expanded gene families were found to be largely enriched in immune-related KEGG pathway categories. Moreover, a total of 18 Toll-like receptor (TLR) genes were identified from the whole genome of S. curriculus. The high-quality genome assembled in this study will provide a valuable resource for accelerating ecological, evolutionary, and genetic research on S. curriculus.

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

Biogeochemistry of sedimentary organic matter in the Yongjiang River estuary in the southern part of Hangzhou Bay, China, since the Late Pleistocene - Dongqin Huang; Xiaolong Li; Zilong Li; Pei Sun Loh; Jianxiong Hu; Jianfang Chen; Yuan-Pin Chang; Chin-Wen Yang; Qin Gao (Journal of Oceanology and Limnology, 2024)

Microbial-mediated oxidative dissolution of orpiment and realgar in circumneutral aquatic environments - Xiaoxu Sun; Duanyi Huang; Yuqing Huang; Max Häggblom; Mohsen Soleimani; Jiayi Li; Zheng Chen; Zhenyu Chen; Pin Gao; Baoqin Li; Weimin Sun (Water Research, 2024)

A novel baking additive: Preparation, characterization, and application of chitosan hydrochloride/carboxymethyl starch sodium nano-gel for wheat bread - Xinlai Dou; Yanling Hao; Ying Sun; Pin Yang; Linlin Liu; Yinyuan He; Yanguo Shi; Chunhua Yang; Fenglian Chen (Food Hydrocolloids, 2024)

The Influences of the COVID-19 Pandemic on Haemophilus parainfluenzae Infection in Children, Henan, China, 2016–2021 - Mengxin Zhang; Meng Sun; Pin Zhang; Huanmin Wang; Xianwei Zhang; Wancun Zhang (Indian Journal of Microbiology, 2024)

Acute hepatic and kidney injury after ingestion of Lepiota brunneoincarnata: Report of 2 cases - JiaJu Zhong; Pin Xu; HaiJiao Li; ChengYe Sun; Yun Tong; QunMei Yao; ChengMin Yu (Toxicon, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Physiological and psychological responses to transitions between urban built and natural environments using the cave automated virtual environment - Di Chen; Jie Yin; Chia-Pin Yu; Shengjing Sun; Charlotte Gabel; John D. Spengler (Landscape and Urban Planning, 2024)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Association of co-exposure to metal(loid)s during pregnancy with birth outcomes in the Tibetan plateau - Lei Zhao; Tiemei Li; Haijing Wang; Yue-Mei Fan; Yuancan Xiao; Xuejun Wang; Shulin Wang; Pin Sun; Pinhua Wang; Zhaxi Jiangcuo; Li Tong; Liehong Wang; et al. (Chemosphere, 2023)

Cell activity manipulation through optimizing piezoelectricity and polarization of diphenylalanine peptide nanotube-based nanocomposite - Huiling Guo; Dong-Min Lee; Pin Zhao; So-Hee Kim; Inah Hyun; Byung-Joon Park; Ju-Hyuck Lee; Huajun Sun; Sang-Woo Kim (Chemical Engineering Journal, 2023)

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

Critical public infrastructure underwater: the flood hazard profile of Florida hospitals - Pin Sun; Rebecca Entress; Jenna Tyler; Abdul-Akeem Sadiq; Douglas Noonan (Natural Hazards, 2023)

Thiobacillus spp. and Anaeromyxobacter spp. mediate arsenite oxidation-dependent biological nitrogen fixation in two contrasting types of arsenic-contaminated soils - Yongbin Li; Lifang Guo; Rui Yang; Zhaohui Yang; Haihan Zhang; Qiqian Li; Zhiguo Cao; Xin Zhang; Pin Gao; Wenlong Gao; Geng Yan; Duanyi Huang; et al. (Journal of Hazardous Materials, 2023)

What factors contribute to the extent of decoupling economic growth and energy carbon emissions in China? - Pinjie Xie; Ningyu Gong; Feihu Sun; Pin Li; Xianyou Pan (Energy Policy, 2023)

Carbon emission reduction policy with privatization in an oligopoly model - Junlong Chen; Chaoqun Sun; Yajie Wang; Jiali Liu; Pin Zhou (Environmental Science and Pollution Research, 2023)

Effects of perfluorooctanoic acid (PFOA) on activated sludge microbial community under aerobic and anaerobic conditions - Duanyi Huang; Rui Xu; Xiaoxu Sun; Yongbin Li; Enzong Xiao; Zhimin Xu; Qi Wang; Pin Gao; Zhaohui Yang; Hanzhi Lin; Weimin Sun (Environmental Science and Pollution Research, 2022)

Keystone taxa and functional analysis in arsenic and antimony co-contaminated rice terraces - Pingzhou Su; Pin Gao; Weimin Sun; Wenlong Gao; Fuqing Xu; Qi Wang; Enzong Xiao; Mohsen Soleimani; Xiaoxu Sun (Environmental Science and Pollution Research, 2022)

Metabolic potentials of members of the class Acidobacteriia in metal‐contaminated soils revealed by metagenomic analysis - Rui Xu; Xiaoxu Sun; Max M. Häggblom; Yiran Dong; Miaomiao Zhang; Zhaohui Yang; Enzong Xiao; Tangfu Xiao; Pin Gao; Baoqin Li; Weimin Sun (Environmental Microbiology, 2022)
Summary The relative abundance of Acidobacteriia correlated positively with the concentrations of arsenic (As), mercury (Hg), chromium (Cr), copper (Cu) and other metals, suggesting their adaptation of the metal‐rich environments. Metagenomic binning reconstructed 29 high‐quality metagenome‐assembled genomes (MAGs) associated with Acidobacteriia , providing an opportunity to study their metabolic potentials. These MAGs contained genes to transform As, Hg and Cr through oxidation, reduction, efflux and demethylation, suggesting the potential of Acidobacteriia to transform such metal(loid)s. Additionally, genes associated with alleviation of acidic and metal stress were also detected in these MAGs. Acidobacteriia may have the capabilities to resist or transform metal(loid)s in acidic metal‐contaminated sites. Moreover, these genes encoding metal transformation could be also identified in the Acidobacteriia ‐associated MAGs from five additional metal‐contaminated sites across Southwest China, as well as Acidobacteriia ‐associated reference genomes from the NCBI database, suggesting that the capability of metal transformation may be widespread among Acidobacteriia members. This discovery provides an understanding of metabolic potentials of the Acidobacteriia in acidic metal‐rich sites.

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Citric acid and AMF inoculation combination–assisted phytoextraction of vanadium (V) by Medicago sativa in V mining contaminated soil - Lang Qiu; Wenlong Gao; Zhigang Wang; Baoqin Li; Weimin Sun; Pin Gao; Xiaoxu Sun; Benru Song; Yanxu Zhang; Tianle Kong; Hanzhi Lin (Environmental Science and Pollution Research, 2021)

Structure and variation of root-associated bacterial communities of Cyperus rotundus L. in the contaminated soils around Pb/Zn mine sites - Pin Gao; Benru Song; Rui Xu; Xiaoxu Sun; Hanzhi Lin; Fuqing Xu; Baoqin Li; Weimin Sun (Environmental Science and Pollution Research, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

Critical review of ARGs reduction behavior in various sludge and sewage treatment processes in wastewater treatment plants - Gang Xue; Mingji Jiang; Hong Chen; Min Sun; Yunfan Liu; Xiang Li; Pin Gao (Critical Reviews in Environmental Science and Technology, 2019)

Characterization of iron-metabolizing communities in soils contaminated by acid mine drainage from an abandoned coal mine in Southwest China - Pin Gao; Xiaoxu Sun; Enzong Xiao; Zhixian Xu; Baoqin Li; Weimin Sun (Environmental Science and Pollution Research, 2019)

Cytochrome P450 2AA molecular clone, expression pattern, and different regulation by fish oil and lard oil in diets of grass carp (Ctenopharyngodon idella) - Xiao-chen Shi; Jian Sun; Ai Jin; Hong Ji; Hai-bo Yu; Yang Li; Xue-xian Li; Pin Liu; Chao Li; Ji-qin Huang (Fish Physiology and Biochemistry, 2018)

Spatiotemporal patterns of drought at various time scales in Shandong Province of Eastern China - Depeng Zuo; Siyang Cai; Zongxue Xu; Fulin Li; Wenchao Sun; Xiaojing Yang; Guangyuan Kan; Pin Liu (Theoretical and Applied Climatology, 2018)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Isolation and Characterization of an Erythromycin-Degrading Strain and Application for Bioaugmentation in a Biological Aerated Filter - Pin Gao; Xin Wei; Chaochao Gu; Xiaoqian Wu; Gang Xue; Weimin Shi; Weimin Sun (Water, Air, & Soil Pollution, 2015)

The spatio-temporal variations of surface water quality in China during the “Eleventh Five-Year Plan” - Jingbo Sun; Yi Chen; Zhao Zhang; Pin Wang; Xiao Song; Xing Wei; Boyan Feng (Environmental Monitoring and Assessment, 2015)

The complete mitochondrial genome of the brown leg mite, Aleuroglyphus ovatus (Acari: Sarcoptiformes): evaluation of largest non-coding region and unique tRNAs - En-Tao Sun; Chao-Pin Li; Liu-Wang Nie; Yu-Xin Jiang (Experimental and Applied Acarology, 2014)

An EGFR gene of the Pacific oyster Crassostrea gigas functions in wound healing and promotes cell proliferation - Lingling Sun; Pin Huan; Hongxia Wang; Fengsong Liu; Baozhong Liu (Molecular Biology Reports, 2014)

The use of allelic imbalance to ascertain cis-regulation for human UGT2B7 in vivo - Pin-Yi Wang; Dezheng Huo; Chang Sun; Olufunmilayo I. Olopade (European Journal of Clinical Pharmacology, 2013)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Electrospun Nanofibers in Oral Drug Delivery - Francis Ignatious; Linghong Sun; Chao-Pin Lee; John Baldoni (Pharmaceutical Research, 2010)

Effects of cyanobacterial toxin microcystin-LR on the transcription levels of immune-related genes in grass carp Ctenopharyngodon idella - Lili Wei; Baojian Sun; MingXian Chang; Yi Liu; Pin Nie (Environmental Biology of Fishes, 2009)

Iron-Deficiency Induces Cadmium Uptake and Accumulation in Solanum nigrum L. - Tong Bao; Lina Sun; Tieheng Sun; Pin Zhang; Zhixin Niu (Bulletin of Environmental Contamination and Toxicology, 2009)

Assessing Genetic Diversity of Chinese Cultivated Barley by STS Markers - Xiwen Chen; Shaoying Guo; Defu Chen; Pin Liu; Xiangdong Jia; Lijun Sun (Genetic Resources and Crop Evolution, 2006)

Gene structure and transcription of IRF-2 in the mandarin fish Siniperca chuatsi with the finding of alternative transcripts and microsatellite in the coding region - Baojian Sun; Mingxian Chang; Dali Chen; Pin Nie (Immunogenetics, 2006)